Addressing environmental misperceptions for nature recovery - Shuo Gao; Sophus O. S. E. zu Ermgassen; Joseph W. Bull; E. J. Milner‐Gulland (Conservation Biology, 2026)
A poorly understood and systemic challenge to global conservation agreements is shifting baseline syndrome (SBS), wherein people misperceive the extent to which nature has changed. This can diminish societal expectations for nature recovery. We broadened the conceptual framing of SBS beyond the more common elements of nature loss to include nature recovery and the cognitive mechanisms underlying misperceptions. To demonstrate the utility of the framework, we surveyed people living in Qunli New Town, Harbin, China. We first conducted in‐depth interviews with a semirandomized sample of 42 people to qualitatively explore the diverse manifestations of environmental misperceptions and the cognitive processes that drive misperceptions in the study area. We then administered an online survey of 1018 people to quantitatively estimate the scale of SBS and identify factors affecting individual misperceptions. The accuracy of these perceptions was determined by comparing participants’ reported environmental conditions with actual measurements. Inaccurate perceptions were linked to media‐based (e.g., television) environmental information sources; direct interaction with nature did not foster ecological understanding in most cases; depth of personal engagement (e.g., interest in local nature and time spent per visit) was associated with such understanding; and cognitive errors underlying environmental misperceptions, including errors of omission and commission, were related to cognitive processes, such as sensation, attention, learning, thinking, and memory. More nuanced, place‐based strategies are needed that explicitly address the structural and cognitive dimensions of environmental misperceptions. Minimizing such misperceptions is important so that people affected by environmental change can better respond to it. This is essential for pursuing resilient, sustainable, and inclusive societies under the Sustainable Development Goals and the Global Biodiversity Framework.